Analysis of The Influence of Halal Tourism on the Interest of Foreign Tourist: Case Study on Islamic Tourism Places in West Sumatra - alfiona, fifa; Febrina Adita Putri; Melisa Anggreni; Restika; Mardhiyya Azhari; Rahma Elsa Fitriani; Rani Ashari Febrian; Zulfa Suryani; Eka Novia Herdiamy; Desma Handayani; Tifany Yeldi Astuti; Vivi Rosdiyanti; Amsah Hendri Doni (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Halal tourism in West Sumatra is currently an attractive nominated among the world community so many foreign tourists go on vacation to tourist attractions in West Sumatra. This study aims to see the influence of halal tourism on the interest of foreign tourist case studies on Islamic tourist attractions in West Sumatra. This research method is quantitative with descriptive analysis and data collection with questionnaires and the level is the Likert scale from correspondent data on tours that have come to West Sumatra, correspondent data as many as 38 tourists. The results of this study are: Based on the ANOVA test, a value of F = 0.197 was obtained with a probability of significance of 0.022, a significance value of 0.022 when compared to a value of <alpha (0.05), then the H0 hypothesis was rejected and the Ha hypothesis was accepted, which means that there is a significant influence on halal tourism on the interest of foreign tourist, a case study on Islamic tourist attractions in West Sumatra. The Level of Influence of Halal Tourism Variables on Foreign tourist to the Islamic Tourism Places in West Sumatra was 0.385 or 38.5% while 61.5% was influenced by other variables not included in this study